Green Framing in Corporate Poultry Videos: An Analysis of Sustainability Messaging - Dylan VanBoxtel; Rebecca Swenson; Garrett Steede (Journal of Applied Communications, 2023)
Large broiler chicken companies have been under pressure by consumers to reduce their carbon footprint, improve animal welfare and labor practices, and enhance environmental quality across the industry. This study examines how large broiler chicken companies have addressed sustainability within video content directed toward consumers and posted on YouTube. To conceptualize this study, we used the 1990 Farm Bill definition of agricultural sustainability. It is important to examine articulations of agricultural sustainability as company messages often incorporate sustainability philosophies and ideologies while referencing specific production practices and goals. This study used qualitative content analysis to analyze 440 videos, and framing analysis to closely examine a subset of 55 videos, from three of the largest broiler chicken companies in the United States. The framing analysis revealed that stewardship, natural state, and catalyst for change were the three most frequently used sustainability frames across the companies. These frames focus on elements of caretaking, responsibility, and public accountability, and apply these ideals to people, chickens, and profit within the organization. Few discussions of environmental stewardship were found within our analysis. While frames were not necessarily connected to production practices, each company did tend to leverage frames in ways that align with brand positioning. Companies should consider implementing discussions of how production practices affect the environment more directly, since protecting the environment and replenishing natural resources are concepts consumers associate with sustainability.
Keywords: Framing; Sustainability; Livestock; Video; Corporate